1970
DOI: 10.1007/bf01742067
|View full text |Cite
|
Sign up to set email alerts
|

Biological transformations associated with weather changes. An hypothesis on the flight activity of WISEANA spp.

Abstract: The increased activity of insects before weather changes, particularly, certain types of weather, has been the subject of theorising that atmospheric e l e c t r i c i t y , among other things, might influence insect activity and behaviour before and during these changes (Fabre 1918;Uvarov, 1931;Wellington, 1957). Henson (1951), Rainey (1951) and Wellington (1957} have studied m a s s weather effects on insects and have shown the apparent effects of approaching and receding weather fronts on insect activity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This indicates that other factors may explain the occurrence of some species. For example, the emergence of some species of hepialid moth from their subterranean tunnels is closely timed to coincide with the passage of weather fronts (Helson & Penman, 1970;Edwards & Green, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that other factors may explain the occurrence of some species. For example, the emergence of some species of hepialid moth from their subterranean tunnels is closely timed to coincide with the passage of weather fronts (Helson & Penman, 1970;Edwards & Green, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is very possible that the behaviours observed in these studies are in fact derivative of ecologically relevant electroreceptive abilities, such as avoidance of predators or hazardous meteorological conditions. Indeed, it has long been speculated that weather‐associated fluctuations in atmospheric electricity may influence the behaviour of insects (Uvarov, 1931; Wellington, 1957; Helson & Penman, 1970). It could certainly be the case that the excessive behavioural thresholds recorded are the result of a lack of stimulus specificity to those encountered in the natural ecology of the animal, particularly in terms of temporal components such as the frequency and envelope modulations of the electrical signal.…”
Section: Electroreceptionmentioning
confidence: 99%
“…According to Helson & Penman (1970) and Carpenter (1978), females of W. copularis begin wing fanning 10 min after emergence and do not usually fly before fanning their wings. McDunnough (1911) observed that a virgin female of a North American hepialid species emerged and ascended a grass stalk.…”
Section: Discussionmentioning
confidence: 99%